Advancing Transparency - Lisa Rammig (A+BE: Architecture and the Built Environment)
Glass is transparent and that differentiates it from most other building materials. As a result it has played a significant role in the development of architecture, given that its use is not only driven by its functionality as a protective layer, but by its ability to transmit light and hence define spaces. The use of glass has typically brought designers, engineers and builders to the limits of their abilities, whether this was driven by the processing and handling of the material, or the limitationin the understanding of its design capacity. The transparency of the material is of incredible value but it also poses challenges when working with glass; The way it is connected is always visible. As a result, the connections and connectivity of glass are one of the most important considerations when designing with it, both technically and architecturally and in particular for structural applications. In the past century, glass has increasingly been used as a structural component. However its inherent brittleness typically still requires opaque metal connections to transfer load. These connections define contemporary glass architecture – firstly, because they are immediately apparent in a transparent structure and, secondly, as they are part of the engineering design language. However, designers and architects are still aiming to increase the transparency of glass enclosures and structures, leading to a demand to further reduce the visibility of structural connections within the glass. This research aims to address the connectivity of glass through experimental testing of heat bonded glass-glass connections that form a fully transparent atomic bond. Applications for transparent connections are addressed through case studies that explore various novel transparent bonding techniques.